Continuing education in times of Covid-19 - Viegas , Graziela Lenz (Seven Editora, 2023)
The chances of contamination of health professionals who work in symptomatic patients are high. The nurse sees in his role as caregiver, leader and educator, a reference in the team, in the prevention of COVID-19. The study is a bibliographical, systematic, and reflective review, using the descriptors Nursing, Continuing Education and COVID-19, accessing and selecting data in the Virtual Health Library. The need to update and modify the practices of health professionals made Permanent Education (PE) a health policy, turning the theme into a challenge to be faced by all health categories. The arrival of the COVID-19 pandemic required a rapid response, especially in diagnosis and preparation to receive the demand. The need to work with the techniques of contagion prevention, especially with the paramentation and undressing, demanded from the Nursing revision of techniques, in the use of the main individual protective equipment. Finally, the review and correction of contagion prevention techniques should be a daily practice, using PE as a resource to promote educational processes. DOI:https://doi.org/10.56238/emerrelcovid19-027